Cannabis for Cognitive Enhancement as a New Coping Strategy? Results From a Survey of Students at Four Universities in Germany. (5th December 2016) - Franke, Andreas G.; Roser, Patrik; Lieb, Klaus; Vollmann, Jochen; Schildmann, Jan
ABSTRACT: Background : Cognitive Enhancement (CE) is often discussed in relation to stimulant drugs, such as amphetamines (AMPH). However, there is some evidence that cannabis (CAN) can be used for CE. Objective : This study compares the knowledge, prevalence, and perceived effects of and factors associated with the knowledge of or use of CAN versus AMPH for CE among undergraduate students at four German universities. Methods : A survey was taken of 1, 538 students at four German universities. It investigated their knowledge and use of CAN and AMPH for CE as well as associated factors. Descriptive and analytic (Mann–Whitney- U test, Fisher's exact test, logistic regression) statistics were obtained using SPSS. Results : Responses were obtained from 1, 026 participants (57.2%) at three universities from the Universitätsallianz Metropole Ruhr (UAR) (Bochum, Dortmund, Duisburg-Essen) and 512 respondents (68.3%) in Mainz. We observed lifetime prevalence rates of 3.5% for the use of CAN and 2.1% for the use of AMPH for the purpose of CE. CAN users perceived pressure to perform as more of a burden than AMPH users (mean: 3.2, CAN users: 4.7, AMPH: 2.9; p =.042). CAN users used the substances for studying for exams significantly less often than AMPH users ( p =.025), and CAN users perceived less of an enhancing effect of the drug compared to AMPH users ( p <.001). Conclusions : A considerable number of students report having used CAN for CE. However, our research indicates differences in perceptions and experiences of CE between CAN and AMPH users. Further research on the role of CAN for CE and conceptual analyses to differentiate between different understandings of CE are warranted.